Increased Reactive Oxygen Species Generation Contributes to the Atherogenic Activity of the B2 Bradykinin Receptor - Perhal, Alexander; Wolf, Stefan; Jamous, Yahya F.; Langer, Andreas; Abd Alla, Joshua; Quitterer, Ursula (Frontiers in Medicine, 2019)
Atherosclerosis and ensuing cardiovascular disease are major causes of death with insufficient treatment options. In search for pathomechanisms of atherosclerosis, we investigated the impact of the B2 bradykinin receptor, Bdkrb2, on atherosclerotic lesion formation, because to date it is not clear whether the B2 bradykinin receptor is atheroprotective or atherogenic. As a model of atherosclerosis, we used hypercholesterolemic ApoE-deficient (apolipoprotein E-deficient) mice, which develop atherosclerotic lesions in the aorta with increasing age. The role of Bdkrb2 in atherosclerosis was studied in ApoE-deficient mice, which were either Bdkrb2-deficient, or had moderately increased aortic B2 bradykinin receptor protein levels induced by transgenic BDKRB2 expression under control of the ubiquitous CMV promoter. We found that Bdkrb2 deficiency led to a significantly decreased atherosclerotic plaque area whereas transgenic BDKRB2 expression enhanced atherosclerotic lesion formation in the aorta of ApoE-deficient mice at an age of 8 months. Concomitantly, the aortic content of reactive oxygen species (ROS) was higher in BDKRB2-expressing mice whereas Bdkrb2 deficiency decreased aortic ROS levels of ApoE-deficient mice. In addition, aortic nitrate as a marker of nitric oxide activity and the endothelial nitric oxide synthase (eNOS) co-factor, tetrahydrobiopterin (BH4) were reduced in BDKRB2-expressing ApoE-deficient mice. The decreased aortic BH4 content could be a consequence of increased ROS generation and down-regulated aortic expression of the BH4-synthesizing enzyme, Gch1 (GTP cyclohydrolase 1). In agreement with a causal involvement of decreased BH4 levels in the atherogenic function of BDKRB2, we found that treatment with the BH4 analogue, sapropterin, significantly retarded atherosclerotic plaque formation in BDKRB2-expressing ApoE-deficient mice. Together our data show that the B2 bradykinin receptor is atherogenic, and the atherosclerosis-promoting function of BDRKB2 is partially caused by decreased aortic BH4 levels, which could account for eNOS uncoupling and further enhancement of ROS generation.